The Effect of Social Media Marketing and Influencer Endorser on Purchase Intention - Nabilla Putri Nofela; Marheni Eka Saputri (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
With a large number of users and a high level of engagement, TikTok is an application that provides enormous opportunities in the business sector, especially in marketing activities. Influencer endorsers are an effective trend for business actors to promote the products they sell. The existence of the TikTok Shop feature on the TikTok application makes it easier for consumers to buy the goods they want. This study will find out how the influence of social media marketing and influencer endorsers on TikTok on purchase intention at TikTok Shop. The research method used is quantitative and the type of research is descriptive and causal. Sampling was done by the non-probability sampling method. Data collection was obtained by distributing online questionnaires to 100 respondents. The data analysis technique used in this research is multiple linear regression analysis. The results show that social media marketing and influencer endorsers on TikTok have a positive and significant effect on purchase intention at TikTok Shop. The results of data processing and data analysis showed that social media marketing and influencer endorsers are contributed to purchase intention.